Signs and Symptoms of Myofascial Pain: An International Survey of Pain Management Providers and Proposed Preliminary Set of Diagnostic Criteria. Issue 9 (5th June 2015) - Rivers, W. Evan; Garrigues, David; Graciosa, Joseph; Harden, R. Norman
Abstract: Objective: Myofascial Pain Syndrome (MPS) is highly prevalent in pain medicine, yet there is no "gold standard" or set of validated diagnostic criteria for clinical or research use. A survey collected clinician perspectives on MPS to foster the development of a formal case definition for empirical validation. Design: International survey Methods: Clinician members of the International Association for the Study of Pain and the American Academy of Pain Medicine received a survey of the symptoms and signs of MPS and expected response to treatment. Write‐in fields were available for each category and to suggest relevant diagnostic studies. Results: Two hundred fourteen responses were received from 4, 143 surveys mailed. The most essential components of MPS were tender spots that recreate symptoms when palpated. MPS was also associated with muscle stiffness, decreased range of motion of the affected joints, worsening symptoms with stress, palpable taut band or tender nodule, and referred pain with palpation of the tender spot. Diagnostic studies are reported to be useful for ruling out other pathology, but not to confirm the presence of the condition. Conclusions: These results were used to propose a set of preliminary diagnostic criteria; expert consensus for case definition and subsequent empirical validation are required for standardization in research and clinical management of MPS.